Adaptive immunity against COVID-19 - Shrestha, Umid Kumar (Journal of Advances in Internal Medicine, 2020)
The adaptive immune response has often been described as the key player in determining the severity of COVID-19 disease. The COVID-19 outcomes seem to be dependent upon the B-cell– and T-cell–mediated adaptive immunity to SARS-CoV-2. Coordinated CD4+ T-cell, CD8+ T-cell, and antibody responses are protective, whereas, the uncoordinated immune responses are associated with the severe form of COVID-19. Multiple human vaccines in clinical trials to counteract SARS-CoV-2 is based upon the neutralizing antibodies directed at the spike protein. The potential therapeutic and preventive monoclonal antibodies used in human clinical trials are also based on the viral neutralization. The vaccines can generate high levels of neutralizing antibodies comparable with or greater than those seen in sera samples from patients. The induction of sufficient CD4+ helper T-cells and inclusion of vaccine boosts, may be needed to maintain levels of anti–SARS-CoV-2 neutralizing antibodies. The COVID-19 vaccines are in rapid development by utilizing the knowledge of adaptive immunity against COVID-19, and we are hopeful to get the effective and safe vaccines for the public use very soon.